Laboratory and Flight Test Analysis of Rubidium Frequency Reference Performance. Issue 2 (5th June 2013) - van, Frank; Craig, Samantha; Pelgrum, Wouter; Ugazio, Sabrina
ABSTRACT The performance of Rubidium frequency standards is well‐documented for stationary operation. In dynamic environments that include changes in orientation, acceleration, temperature, pressure, and magnetic field, the performance of frequency references for position, velocity, and timing applications is not well characterized in the literature. This paper includes results from laboratory and flight test experiments. Laboratory tests were conducted to characterize Rubidium oscillator performance under varying gravity and magnetic field conditions. Three Rubidium oscillators were flight tested. Each of the oscillators was connected to a GPS receiver for error characterization. The frequency stability performance is profiled against the flight dynamics based on a navigation‐grade inertial navigation system. The goal of the paper is to increase the awareness of Rb oscillator error sources that affect in‐flight frequency stability, with an emphasis on gravity sensitivity and magnetic field susceptibility. Copyright © 2013 Institute of Navigation.